Rates of Return to Social Protection Social Cash Transfers in Uganda - Dietrich, Stephan; Gassmann, Franziska (United Nations University, 2018)
This policy brief is part of a wider research project entitled ‘Building the Economic Case for Investments in Social Protection’. The research aims at demonstrating the potential impacts of social protection on inclusive growth. The project is a collaborative effort between the Maastricht Graduate School of Governance at the University of Maastricht and United Nations University-MERIT, NL; the Global Development Institute at the University of Manchester, UK; the School of Social Science at the University of Makerere, Uganda; and the Expanding Social Protection Programme of the Ugandan Ministry of Gender, labor and Social Development. This project is part of the research agenda of the Knowledge Platform Inclusive Development Policies and funded by the Ministry of Foreign Affairs of the Netherlands through the NWO- WOTRO programme.